Comparative Study of Knowledge Level with HIV/AIDS Transmission Prevention Behavior in Junior High School Adolescents in 2022 - Chairani, Reni; Izzah, Alifia Nurul (Asian Journal of Pharmaceutical Research and Development, 2023)
The problem of HIV/AIDS is still a global health problem, including in Indonesia, which is a country with a high prevalence of HIV/AIDS. Adolescents are one of the groups at risk of contracting HIV/AIDS. The provinces of West Java and DKI Jakarta were provinces that contributed the most cases of HIV/AIDS in recent years. It is necessary to study the level of knowledge and behavior of junior high school youth groups in Depok and Jakarta regarding the prevention of HIV/AIDS transmission. The comparative study method with a cross sectional approach is the research design carried out in this study. by comparing two different groups. The characteristics of the 2 different groups of respondents in this study consisting of age, gender and parental education are the same. The level of knowledge of the respondents in this study had a low level of knowledge equality. The low level of knowledge among junior high school adolescents in Jakarta dominates (64%) compared to junior high school adolescents in Depok (50%) as evidenced by high risk behavior more in junior high school adolescents in Jakarta. The results of the Chi-Square test show that there is a relationship between the level of knowledge and the behavior of preventing HIV/AIDS transmission, because the p value = 0.000 (p value 0.05. In order to increase knowledge about adolescent health, especially HIV/AIDS, which is one of the phenomena prioritized diseases in the world and in Indonesia Health education needs to be included in the education curriculum in schools so that adolescents have good health information and are expected to influence good behavior for adolescents in the future.